Les conseils consultatifs régionaux : vers une nouvelle gouvernance pour les pêches de l’union européenne ? - Sarah Lelong (VertigO)
Oceans and fisheries all over the world are endangered by threats as pollutions, global warming and overfishing. Scientists are more and more worried about the dangerous evolution of these problems. Since the 70’s, the technological growth and the incredible progress on fishing gears lead the worldwide fleet to overcapacity and overexploitation of almost 75 percent of fish stocks. The European common fisheries policy tries since 2002 to have a better acceptance of environmental concern. But the problem is very complexe because of so many conflicts between the stakeholders (scientists, fishermen, decision-maker…). As a consequence, the regional advisory councils (RACs) were created as communication cells between the different bodies engaged into the decision-making process and information exchange. Since these cells are working at a regional level, they enable the participation of professional to the Communitarian decision process in the field of fisheries and then facilitate the acceptation of rules as well as environmental objectives. A first assessment of their active work in the last past years can justify good hope towards a new way of governance.